2017
DOI: 10.1186/s12879-017-2510-x
|View full text |Cite
|
Sign up to set email alerts
|

Observed versus predicted cardiovascular events and all-cause death in HIV infection: a longitudinal cohort study

Abstract: BackgroundThe aim of the study was to assess the applicability of an algorithm predicting 10-year cardiovascular disease (CVD) generated in the setting of the Framingham Heart Study to a real-life, contemporary Italian cohort of HIV-positive subjects.MethodsThe study was an observational longitudinal cohort study. The probability for 10-year CVD events according to the Framingham algorithm was assessed in 369 consecutive HIV-positive participants free from overt CVD enrolled in 2004, who were followed for a me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 19 publications
3
35
0
Order By: Relevance
“…Those aged ≥ 51 years had 5.5 times the hazard compared with those aged < 40 years. This is consistent with other studies indicating the effect of aging on the increased risk of CVD . Younger median age might also, in combination with prescription of ART regimens that are less detrimental to cardiovascular health, explain the reduced CVD hazard in the group of patients who started ART more recently.…”
Section: Discussionsupporting
confidence: 92%
“…Those aged ≥ 51 years had 5.5 times the hazard compared with those aged < 40 years. This is consistent with other studies indicating the effect of aging on the increased risk of CVD . Younger median age might also, in combination with prescription of ART regimens that are less detrimental to cardiovascular health, explain the reduced CVD hazard in the group of patients who started ART more recently.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with the pooled analysis of Janssen-sponsored clinical trials, higher CVD event reporting rates were observed during the period 2006–2009, when only twice-daily darunavir/ritonavir 600/100 mg was available, compared with the reporting rates for 2010–2016, when both twice-daily darunavir/ritonavir 600/100 mg and once-daily darunavir/ritonavir 800/100 mg were available. Overall, CVD event reporting rates with darunavir were significantly lower than the observed rates of CVD events in the general HIV-1–infected population [ 43 , 44 ]. The data mining analysis of post-marketing pharmacovigilance databases [FAERS (2016 Q2) and VigiBase (2016 Q4)] exhibited disproportionality of CVD events mainly for first-generation PIs (e.g., indinavir, nelfinavir, ritonavir, saquinavir).…”
Section: Discussionmentioning
confidence: 99%
“…There are no prior studies directly examining this in PLHIV. Considering that males and females tend to have similar improvements in cardiovascular events with aggressive secondary prevention strategies in the general population, there is need for further research specific to our patient cohort . We hypothesize that the higher hospital cost in males is due to related difference in invasive vs noninvasive management strategies between males and females in our study.…”
Section: Discussionmentioning
confidence: 91%
“…HAART may also independently potentiate low‐grade arterial inflammation . This population has a preponderance of traditional risk factors for CVD that strongly predict CVD events in both HIV‐infected and uninfected populations alike . The increased risk of AMI in those infected with HIV has been the subject of multiple cohort studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation